The Philosophy of the Pengurip Gumi Ceremony at Pura Luhur Batukaru In the Contemporary Era - I Ketut Subagiasta (IAHN-TP Palangka Raya, 2022)
An article related to Hindu rituals taking place in Bali Indonesia, carried out in the Batukaru Temple area in the Wongaya Gede Village Penebel area of ??Tabanan Bali Indonesia named or writing entitled